Understanding the framework for intergovernmental interactions in the implementation of Nigeria’s Agricultural Transformation Agenda - Olomola, Aderibigbe (International Food Policy Research Institute, 2015)
This study focuses on intergovernmental interactions in Nigeria’s Agricultural Transformation Agenda (ATA). ATA may not be able to achieve its desired objectives unless the intergovernmental and inter-agency interactions are well understood, coordinated, and integrated into the design and implementation of the various ATA programs, especially those that are still being developed. Unfortunately, the interactions among the three tiers of government in Nigeria is still not recognized by policy makers as a major issue in refining the design of the transformation process and reinforcing it. No tier of government acting alone in making decisions that affect all three tiers of government can create an environment that will be sufficiently enabling to ensure that farmers and other beneficiaries of ATA initiatives receive the maximum benefits obtainable. If the buy-in of a particular level of government is not properly and meaningfully secured, implementation of programs can be fraught with de-lays and avoidable costs. These may jeopardize the sustainability of ATA.